Cytokinin regulates the activity of the inflorescence meristem and components of seed yield in oilseed rape. (10th September 2020) - Schwarz, Ireen; Scheirlinck, Marie-Therese; Otto, Elisabeth; Bartrina, Isabel; Schmidt, Ralf-Christian; Schmülling, Thomas
Abstract: The number of flowers and seed-bearing structures formed by the inflorescence meristem and the formation of ovules in the female reproductive part of the flowers are important yield-related traits of crop plants. It has been shown that cytokinin is a pivotal factor regulating these traits. Here, we explore the impact of mutation of CYTOKININ OXIDASE / DEHYDROGENASE ( CKX ) genes encoding cytokinin-degrading enzymes on these yield-related traits in oilseed rape ( Brassica napus L.). We describe the identification of four BnCKX3 and two BnCKX5 genes as regulators of reproductive development in the allotetraploid B. napus . RNA-seq analysis and in situ hybridization showed expression of these genes in reproductive organs. Loss-of-function mutants for each of these CKX gene copies were identified by targeting induced local lesions in genomes (TILLING) and combined by crossing. Sextuple ckx3 ckx5 mutants showed an increased cytokinin concentration and larger and more active inflorescence meristems. They also produced up to 72% more flowers with gynoecia containing 32% more ovules and up to 54% more pods on the main stem. The weight of seeds harvested from the main stem of plants grown in the greenhouse or in the field was increased by 20–32%. Our results show that cytokinin regulates inflorescence meristem and placenta activity in oilseed rape. The work demonstrates the potential to achieve yield enhancement in a dicot crop plant by modulating the cytokinin status through mutagenesis of specific CKX genes. Abstract : Mutation of all six cytokinin-degrading CKX3 and CKX5 genes of Brassica napus L. increased the activity of the inflorescence meristem enhancing yield-related traits during reproductive development.